One-Step Synthesis of 1H-Imidazo[1,5-a]imidazole Scaffolds and Access to their Polyheterocycles - Loubidi, M.; Lorion, M.; El Hakmaoui, A.; Bernard, P.; Akssira, M.; Guillaumet, G. (Synthesis, 2019)
In this work, we continue our adventure in the chemistry of 5-5 tri-nitrogen bicycles. We disclose herein a one-step reaction to synthesize 1H-imidazo[1,5-a]imidazoles with different substituents introduced through the use of a wide range of aldehydes and isocyanides by using a Groebke–Blackburn–Bienaymé multicomponent reaction. The aim is to build a new library of 1H-imidazo[1,5-a]imidazole scaffolds. This bicycle was then modified to access new nitrogen-containing polycyclic compounds.
Keywords: imidazo[1,5-a]imidazole; polyheterocycles; Buchwald cyclization; MCRs; imidazo[5′,1′:2,3]imidazo[4,5-b]indole